Vida Saludable: Monitoreando la presión arterial desde la casa: FCS8882-Span/FY1130, 11/2009 - Shelnutt, Karla P. (EDIS, 2009)
FCS8882Span, a 2-page fact sheet by Karla P. Shelnutt, is the Spanish language version of FCS8882/FY1126 Healthy Living: Monitoring Your Blood Pressure at Home. It provides instructions and explanations of blood pressure readings, along with a blank blood pressure log. Published by the UF Department of Family Youth and Community Sciences, November 2009.